SEXUAL AND GENDER HARASSMENT IN THE WORKPLACE IN SPAIN - Quesada, Salvador Peran (European Scientific Journal, ESJ, 2013)
The Spanish Organic Law 3/2007 for the Effective Equality between Women and Men has introduced the concepts of sexual and gender harassment into the Spanish legal system, thus transposing EU directives on this subject into our domestic legal system. The first important consequence of this law is that these two actions are considered discriminatory, leading to the activation of anti-discriminatory legal and institutional mechanisms. The question remains as to whether the legal sanction – including the preventive measures to be adopted by companies – and the remedial measures will suffice to achieve the desired aim, or whether there will be the need to reinforce these legal entities. The ultimate aim is to promote changes in social behavior that will enable the creation of a culture of respect for equality in the workplace. The present paper aims to propose a reflection on the above-mentioned two legal entities in the Spanish legal system from three approaches, which are necessary and complementary: gender perspective, mainstreaming and a comprehensive approach. The combination of these approaches accounts for a new approach, which is important, as it reinforces the action against the social norms on which gender discrimination is based.